Synergies of Adjacent Sites in Atomically Dispersed Ruthenium toward Achieving Stable Hydrogen Evolution - Li, Chunmei; Su, Nan; Wu, Huihui; Liu, Chunbo; Che, Guangbo; Dong, Hongjun (Inorganic chemistry, 2022)
It is a challenge to fabricate atomically dispersed metal clusters in polymeric carbon nitride (PCN) for durable photocatalytic reactions owing to the thermodynamic stability limitation. Herein, atomically dispersed Ru clusters are implanted into the PCN skeleton matrix based on an ionic diffusion and coordination (IDC) strategy, the stability of which is improved owing to the robust Ru–N bonds in the formed RuN4 and RuN3 configurations. Additionally, RuN4 and RuN3 as charge transport bridges between two adjacent melon strands efficaciously conquer hydrogen bond restriction in the skeleton to facilitate the in-plane mobility and separation of charge carriers. Moreover, the synergistic effect of adjacent Ru atoms is triggered on the assembled RuN3–RuN4 and RuN3–RuN3 in the atomically dispersed Ru clusters to significantly decrease hydrogen adsorption energy. As a result, the optimal PCN-Ru photocatalyst achieves nearly 6 times higher than the photocatalytic hydrogen evolution (PHE) rate of the Pt/PCN benchmark and maintains the long-term stable running for 104 h of 26 cycles; its overall PHE performance is far superior to the most of single atoms supported on g-C3N4 photocatalysts reported. The findings here gain new insight into the preparation strategy, structure configuration, and reaction mechanism for atomically dispersed metal clusters supported on PCN, which further stimulates the intensive investigations toward developing more efficient and stable PCN-like photocatalytic materials.